Financial Distress Prediction Analysis Using the Zmijewski Method - Umar, Wahyuni; Muchran, Muchriana; Ridwan, Mukminati (Contemporary Journal on Business and Accounting, 2024)
Purpose – The study aims to predict bankruptcy in pharmaceutical companes listed on the Indonesian Stock Exchange (IDX) for the 2019-2922 period using the Zmijewski method. Design/methodology/approach – The research method used in this study is quantitative research with descriptive analysis. The population in this is study were 11 pharmaceutical companes listed on the Indonesia Study Exchange with a sample 10 companes. The sampling technique used this study was purposive sampling Findings – The result of this study is that in 2019-2020, all companes are in safe state or not in a state of financial distress. In 2021, there 8 pharmaceutical companes in a safe state and there 2 pharmaceutical companes in a state of financial distress. In 2022, there are 9 companes in a safe state and there is 1 company in a state of financial distress. Originality – Sources of data used in this study were secondary data with documentation techniques where data is obtained or collected by previous researchers from existing sources. Keywords: Financial Distress, Zmijewski X-Score, Pharmaceutical Companes Paper Type Research Result